Eudemonism of private detective activity - Horielova, V. (Університет «КРОК», 2018)
The article is devoted to the study of eudemonism as a special element of ethics and morality of the private detective

Стаття присвячена дослідженню евдемонізму як особливого елементу етики та моралі приватного детектива.
Keywords: Private detective activity; private detective; evdemonism; ethics; morality; приватна детективна діяльність; приватний детектив; евдемонізм; етика; мораль